Kymograph-based indicator for assessing articulatory motion in repetitive speech production - Oyama, Jin; Sun, Jing; Hayashi, Ryoko; Kitamura, Tatsuya (Acoustical Science and Technology, 2025)
This study aimed to develop an indicator for assessing articulatory motion during fast and repetitive syllable production, focusing on fluency, periodicity, and consistency. The method utilizes a kymograph derived from the ultrasound imaging of tongue movements in the midsagittal plane. The kymograph was generated by juxtaposing pixels along an observation line through the point of the greatest tongue movement. Periodic patterns in the kymograph indicate controlled, consistent tongue and mandibular movements, whereas nonperiodic patterns suggest speech disturbances. The method employs power spectral image, obtained through two-dimensional discrete Fourier transforms of the kymograph. The resulting power spectrum represents the periodic components in the horizontal direction of the kymograph, with prominent peaks indicating consistent patterns. To validate the method, the authors analyzed ultrasound movies of healthy Japanese speakers—both fluent speakers and those who experienced a sense of speech clumsiness—producing repetitive syllables (/aka/, /aga/, /ata/, and /ada/). The results demonstrated the effectiveness of the indicator in distinguishing between periodic and nonperiodic tongue motions. This approach shows promise for application to real-time MRI movies, potentially opening new avenues for the in-depth analysis of motor speech function. This indicator contributes to the assessment and quantification of the articulatory motion.